IMMUNIZATION COVERAGE IN ETAWAH: A BORDER DISTRICT OF UTTAR PRADESH - Singh, C M; Kaushik, Amit; Jain, Pankaj Kumar; Kumar, S; Srivastava, Dhiraj Kumar; Singh, Naresh Pal; Chandra, S; Singh, A P (Indian Journal of Community Health, 2012)
Research question: What is the coverage of immunization among children of 12-23 months age group in rural Etawah (a border District of Uttar Pradesh)? Objectives: 1. To assess the immunization coverage among 12-23 months age group children in rural Etawah. 2. To study the association of different socio-demographic factors with utilization of immunization services. Study Design: A community based cross sectional study. Setting: The present study was conducted in Saifai Block of District Etawah. Participants: Two hundred and ten children of 12-23 months were included in the study. Results: The percentage of completely immunized children was found to be 40%. The present study revealed that approximately 79.0% children were immunized against BCG, while the corresponding figure for measles vaccination was just 42.4%. Drop-out rate for complete immunization was 48.1%. Conclusion: Overall coverage of immunization services among children aged 12-23 months was lower than the national figures for rural Etawah. Literacy status of parents was significantly associated with the percentage of fully immunized children and the drop-out rate was also found to be higher among children of illiterate mothers. So there is need and scope of more focused Information, education and communication efforts towards parents regarding immunization services.